Learning for Success: Distance Education Students’ use of their Learning Materials - Smith, A.; Smith, E. (Journal of University Teaching and Learning Practice, 2006)
This paper reports the results of a research project investigating the use that Distance Education (DE) students at university make of the learning materials that are supplied to them. The research is based on a survey of 998 DE students enrolled in ten undergraduate subjects spread across all five Faculties at Charles Sturt University (CSU) in New South Wales, Australia. CSU is Australia’s largest DE provider of higher education. The project addressed the following questions: • The extent to which DE undergraduate students use their learning materials. • The extent to which students undertake the learning activities that are often incorporated in learning materials. • The extent to which students obtain learning materials beyond the printed learning materials, especially their use of library facilities and the internet to research topics in their study programs. • The way in which DE undergraduate students approach their study and the study strategies that they adopt. The paper reports the major conclusions from the survey. It was found that the majority of students read most or all of the learning materials that were sent to them. They relied heavily upon the prescribed textbooks, did some additional reading as recommended, to a limited extent carried out additional reading beyond that recommended, and worked through the provided learning materials in a methodical manner. They generally completed, in their minds if not always on paper, the study tasks embedded in the learning materials. Those students that read less and paid less attention to study tasks tended to study in a way that was focused on passing assessment tasks. Overall the study provides a strong argument for the retention of printed learning materials as students seem to work well with them, and the more effectively students use them the better they seem to perform.